Testicular Germ Cell Tumors in Adolescents – Results of the Protocol MAHO 98 and the Identification of Good Risk Patients - Göbel, U.; Calaminus, G.; Haas, R.; Teske, C.; Schönberger, S.; Schneider, D. T.; Leuschner, I.; Harms, D. (Klinische Pädiatrie, 2014)
Background: In adolescents aged 10–15 years germ cell tumors of the testis (TGCT) are rare and information for a risk adapted therapy limited.Aims of the study: The protocol MAHO 98 for patients (pts) with TGCTs is stratified according to age, stage and histology. Pts ≥10 years received after tumororchiectomy 2 courses (crs) PVB and restaging. Residual tumor was resected and therapy continued in regard to inital stage and response.Chemotherapy: PVB: cisplatin (20 mg/m²/day 1–5), vinblastine (3 mg/m²/day 1+2), and bleomycin (15 U/m²/day 1–3). For consolidation 1 crs PVB has been given to stage II patients with CR. In case of PR, 2 crs PEB (vinblastine substituted by etoposide 100 mg/m²/day 1–3) or relapse 3 crs PEI (bleomycin substituted by ifosfamide 1 500 mg/m²/day 1–5) were given.Results: Between Jan 1998 and Dec 2005, 34 pts (≥10 year) were registered, 31 fulfilled the inclusion criteria. Median age: 15;6 years; months (range 13;5–20;2 ). Lugano staging: IA n=14, IB n=2, IC n=3, IIA n=4, IIB n=6, IIC n=1, IIIC n=1. The stage IIIC pt received preoperative chemotherapy, all other pts had tumororchiectomy first. Residual tumor after 2 crs PVB was detected in 4 pts and was resected. Late relapses occurred in 2 pts and were cured by additional therapy. All patients are surviving.Conclusion: Young patients with TGCT stage I and II have an excellent prognosis and further reduction of therapy has to be considered.
Keywords: testicular germ cell tumor; stratified therapy in adolescents; preoperative chemotherapy; response rate